On the chances and challenges of combining electron‐collecting nPOLO and hole‐collecting Al‐p+ contacts in highly efficient p‐type c‐Si solar cells - Peibst, Robby; Haase, Felix; Min, Byungsul; Hollemann, Christina; Brendemühl, Till; Bothe, Karsten; Brendel, Rolf (Progress in photovoltaics, 2023)
ISFH is following a distinct cell development roadmap, which comprises—as a short‐term concept—the combination of an n‐type doped electron‐collecting poly‐Si on oxide (POLO) junction with an Al‐alloyed p+ junction for hole collection. This combination can be integrated either in front‐ and back‐contacted back junction cells (POLO‐BJ) or in interdigitated back‐contacted cells (POLO‐IBC). Here, we present recent progress with these two cell concepts. We report on a certified M2‐sized 22.9% efficient POLO‐BJ cell with a temperature coefficient TCη of only −(0.3 ± 0.02) %rel/K and a certified 23.7% (4 cm2 d.a.) efficient POLO‐IBC cell. We discuss various specific conceptual aspects of this technology and present a simulation‐based sensitivity analysis for quantities related to the quality of the hole‐collecting alloyed Al‐p+ junction which are subject to continuous improvement and thus hard to predict exactly. We report that the measured pseudo fill factor values decrease more due to metallization than would be expected from recombination in the metallized regions with an ideality factor of one only. The gap to pseudo fill factor values that are theoretically achievable at the respective open‐circuit voltages is 1.1%abs (Ga‐doped wafer) for POLO‐IBC and 1.4%abs (B‐doped wafer) to 2%abs (Ga‐doped wafer) for POLO‐BJ. With an embedded blocking layer for Ag crystallites in the poly‐Si, we present a concept to reduce this gap. In this overview, we report on efficiencies up to 22.9% (23.7%) on POLO‐BJ (POLO‐IBC, d.a. 4 cm2) and a low‐temperature coefficient of only −(0.3 ± 0.02)%rel/K and show that the efficiencies could be improved up to 24.6% (25.4%) when improving the pseudo fill factor and the quality of the Al‐p+ contacts.